Corrosion kinetics of carbon steel in hydrochloric acid and its inhibition by recycling Salbutamol extracted from expired Farcolin drug - Arej S. Al-Gorair; Rasha Felaly; Nahed Fouad; Salih S. Al-Juaid; Doaa F. Seyam; Norhan Saadan; Ali Y. El-Etre; Elsayed M. Mabrouk; Metwally Abdallah (Green Chemistry Letters and Reviews)
Salbutamol, which has nontoxic properties, was effectively extracted from expired Farcolin and was evaluated as an inhibitor against carbon steel (CSt) dissolution in 1.0 M HCl solution. Some technologies were applied to determine the inhibition efficacy of Salbutamol such as weight loss (WL), potentiodynamic polarization (PP), electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM). Also, FTIR, 1HNMR, and mass spectroscopy were used to clarify the structure of Salbutamol. The findings indicate that CSt can profit significantly from the recycling of Farcolin medicine and that Salbutamol may be extracted and employed as a CSt corrosion inhibitor. The efficiency of the inhibition improved with an increase in the dosage of salbutamol, polarization resistance and lowering corrosion current density, WL, and temperature. It’s reached 89.65% at a dose of 200 ppm using the EIS technology. The inhibition impact of Salbutamol was interpreted due to its spontaneous adsorption on the CSt/electrolyte interface, in accordance with Langmuir isotherm. Salbutamol was classified as a mixed inhibitor. In addition, how temperature affects the corrosion rate is considered by calculating and discussing some thermodynamic parameters.